HS1-RIV: Improved Efficiency for Authenticated Encryption - Bhardwaj, Abhishek; Som, Subhranil; K. Muttoo, S (International Journal of Engineering and Technology, 2018)
Encryption was â€œneed of the hourâ€ when it was invented but with the progress of time researchers have shown that it is not very effective when implemented alone. Many attacks are present in the present time, which can break any simple encryption in no time. Therefore, researchers have proposed and proved various techniques, which can work along encryption and can increase security by many folds. This paper aims at bringing essence of this evolution and benefits that tag along with it in one document. Various researchers have different point of view regarding the use of techniques and their benefits along with it, some of those point of views and their reasons are given in this paperÂ Â
Keywords: Authenticated Encryption; Subtle Authenticated Encryption; Robust Authenticated Encryption; Initialization vector; Hash Stream 1 (HS1); SIV; RIV.